Thank You to Our 2020 Peer Reviewers. Issue 3 (15th March 2021) - Manighetti, Isabelle; Abercrombie, Rachel; Ben‐Zion, Yehuda; Bernabé, Yves; Bostock, Michael; Dekkers, Mark; Parman, Stephen W.; Schmitt, Douglas; Tregoning, Paul
Abstract: Members of the editorial board of JGR‐Solid Earth express their appreciation to those who served as peer reviewers for the journal in 2020. Plain Language Summary: The editorial board of JGR‐Solid Earth thanks those who served as peer reviewers for the journal in 2020. Key Points: Thank you to the reviewers of articles submitted to JGR‐Solid Earth